2021
DOI: 10.5115/acb.20.261
|View full text |Cite
|
Sign up to set email alerts
|

Body donation trends in Yonsei University: a statistical analysis of donor records

Abstract: Body donation trends in Korea have changed significantly over the last 3 decades. Establishing a body donation system will promote donations to universities for academic purposes. Yonsei University College of Medicine started its own body donation system in 1992, including documenting donors' records. However, there has been no reported attempt to analyze the trend of these records, which could provide noteworthy information that can be interpreted for medical advances. This study performed a statistical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…The relevance of donation programs to supply demands of bodies and anatomical specimens to teaching institutions in different countries and regions worldwide is widely evident and validates the current findings [ 13 , 27 , 44 - 46 ]. At the University of Otago, in New Zealand, the bequest program of the School of Medical Science has been active since 1943, with more than 140 annual registers in the last decades, and also with an approximate reception of 3,000 bodies [ 45 ].…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The relevance of donation programs to supply demands of bodies and anatomical specimens to teaching institutions in different countries and regions worldwide is widely evident and validates the current findings [ 13 , 27 , 44 - 46 ]. At the University of Otago, in New Zealand, the bequest program of the School of Medical Science has been active since 1943, with more than 140 annual registers in the last decades, and also with an approximate reception of 3,000 bodies [ 45 ].…”
Section: Discussionsupporting
confidence: 83%
“…At the University of Bologna, in Italy, the authors observed an increase from 12 to 431 living donors between the creation of its bequest program in 2013 and the first trimester of 2020 [ 13 ]. The number of body donations in Korea increased from 7 to 128 annually at the Yonsei University College of Medicine between 1992 and 2019, reaching a total of 2415 donors [ 27 ]. In Brazil, the UFCSPA used to receive about 5 donors registers a year.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations